PENGARUH STRATEGI KOMUNIKASI PEMASARAN TERHADAP LOYALITAS PELANGGAN PADA ALFAMART ZENI KOSTRAD SRENGSENG SAWAH JAKARTA SELATAN - Nova Darmanto; Dadang Syaputra; Muhamad Ridwan (Politeknik Negeri Media Kreatif, 2022)
ABSTRACTÂ This study aims to determine how much influence marketing communication strategies have on customer loyalty Alfamart Zeni Kostrad Srengseng Sawah. The population in this study were all Alfamart customers with a sample of 200 respondents and the technique used was random sampling. Data collection techniques used in this study were interviews with the help of questionnaires and documentation. The answers given by the respondents were analyzed quantitatively using the SPSS program. The quality of the research data was tested with validity and reliability tests and linear regression analysis tests. From the results of the analysis, the indicators in this study were declared valid and reliable. The test results state that the marketing communication variable has a positive and significant effect on customer loyalty. The author's suggestion is that Alfamart Zeni Kostrad Srengseng Sawah must maintain and even improve marketing communication strategies so that it will always be able to maintain customer loyalty and must fix problems related to indicators that can affect customer loyalty such as targeting, segmenting and positioning, this is very important because it looks at consumer behavior now which also prioritizes the comfort and friendliness of employees to be able to provide comfort in addition to the main indicators such as product and priceÂ Keywords: Strategy, marketing communication and customer loyalty